2006
DOI: 10.1128/aem.01162-06
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Fluorobenzene by Rhizobiales Strain F11 via ortho Cleavage of 4-Fluorocatechol and Catechol

Abstract: The aerobic metabolism of fluorobenzene by Rhizobiales sp. strain F11 was investigated. Liquid chromatography-mass spectrometry analysis showed that 4-fluorocatechol and catechol were formed as intermediates during fluorobenzene degradation by cell suspensions. Both these compounds, unlike 3-fluorocatechol, supported growth and oxygen uptake. Cells grown on fluorobenzene contained enzymes for the ortho pathway but not for meta ring cleavage of catechols. The results suggest that fluorobenzene is predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The cleavage of the carbon-fluorine bond is especially interesting in view of its kinetic stability and high bond energy. Defluorination of fluoroaromatics can occur prior to ring cleavage, e.g., via an oxygenase that defluorinates fluorobenzoate (11,36) or fluorobenzene (8). In other cases, defluorination occurs after ring cleavage via the formation of fluorinated muconolactones (42), which can be produced from 4-fluorobenzoate (19) and fluorobenzene (8) via 4-fluorocatechol.…”
mentioning
confidence: 99%
“…The cleavage of the carbon-fluorine bond is especially interesting in view of its kinetic stability and high bond energy. Defluorination of fluoroaromatics can occur prior to ring cleavage, e.g., via an oxygenase that defluorinates fluorobenzoate (11,36) or fluorobenzene (8). In other cases, defluorination occurs after ring cleavage via the formation of fluorinated muconolactones (42), which can be produced from 4-fluorobenzoate (19) and fluorobenzene (8) via 4-fluorocatechol.…”
mentioning
confidence: 99%
“…Small amounts of cis-dienelactone were detected as a deadend metabolite during growth of Rhizobiales strain F11 on fluorobenzene (Carvalho et al 2006), complying with its role as a minor byproduct rather than a true intermediate of productive 4-fluorocatechol degradation (a possible participation of trans-dienelactone was not addressed). Consistently with this interpretation, no cis-or trans-dienelactone transforming activity was detectable in cells of the fluorobenzoatedegrading strain FLB300 (Engesser et al 1990a).…”
Section: Halogenated Catechol Derivatives: 3-fluorocatecholmentioning
confidence: 83%
“…The studies, carried out by Hamilton et al [115,116] with 13 C-and 2 H-labeled precursors, demonstrated a high rate of conversion of glycines and pyruvates into FA and 4-FT, with the carbon atoms of FA and C-3 and C-4 of 4-FT being derived from C-2 of glycine or from C-2 and C-3 of pyruvate, indicating that the substrate for the fluorinating enzyme should be an intermediate between glycerol and pyruvate. It was also shown that the integration of 13 C in the C-1 and C-2 of FA always paralleled that in the C-3 and C-4 of 4-FT, indicating the existence of just one fluorinating enzyme in S. cattleya. Later, Moss et al [117] showed that fluoroacetaldehyde is a common precursor of both FA and 4-FT.…”
Section: -Fluorothreonine and Fluoroacetatementioning
confidence: 84%
“…For many fluoro-organics biodegradation is completely unknown. Monofluorinated compounds like fluorophenols [7][8][9][10], fluorobenzenes [11][12][13][14][15], fluorobenzoates [16][17][18], fluoroanilines [19][20][21], and fluoroacetate (FA) [22][23][24] are more likely to be biodegraded, while polyfluorinated compounds are more prone to be recalcitrant, as is the case with perfluorinated compounds. [1,25,26] In contrast to the countless number of man-made fluorinated molecules, fluorine is rarely found in natural compounds, in spite of constituting the 13th most abundant element on Earth.…”
Section: Introductionmentioning
confidence: 99%